Review Article: Tatalaksana Hipertensi Pada Kehamilan - Santika, Mesi; Oktafany, Oktafany; Damayanti, Ervina; Sukohar, Asep (Medula, 2024)
Hypertension is an increase in blood pressure exceeds normal limits i.e. blood pressure ≥140/90 mmHg. Hypertension in pregnancy consists of four categories, namely preeclampsia/eclampsia, chronic hypertension, superimposed preeclampsia with chronic hypertension and gestational hypertension. Hypertension in pregnancy should be managed appropriately to reduce maternal and fetal morbidity and mortality rate, i.e. by preventing women from getting the risks of increased blood pressure, preventing disease progression and preventing the development of seizure and considering termination of pregnancy in life threatening situation for maternal and fetal health. The purpose of this literature review is to determine the management of hypertension in pregnancy. The method used is a literature review, i.e. by searching for both international and national literature using the google scholar and pubmed databases with the keyword "Management of hypertension in pregnancy". There are two categories of antihypertensive drug use in pregnancy, i.e. antihypertensive drugs that can be safely used in pregnancy and antihypertensive drugs to avoid in pregnancy. Antihypertensive drugs that are safe to use are labetalol, nifedipine, methyldopa, hydralazine, magnesium sulfate and prazosin. Antihypertensive drugs that should be avoided are angiotensin-converting enzyme inhibitor, angiotensin receptor blocker, diuretic, beta blocker (except labetalol) and calcium-channel blocker (except nifedipine and diltiazem).